Testing a Model of Successful Aging on Masters Athletes and Non-Sporting Adults. Issue 1 (2nd January 2021) - Geard, David; Rebar, Amanda L.; Dionigi, Rylee A.; Reaburn, Peter R. J.
ABSTRACT: Purpose : To test confirmatory factor analyses of successful aging composed of physical, psychological, cognitive, and social functioning factors in masters athletes ( n = 764) and non-sporting adults ( n = 404), and compare the physical, psychological, cognitive, and social functioning of masters athletes versus non-sporting adults. Method : Self-reported cross-sectional data were analyzed with confirmatory factor analyses. Results : Physical, psychological, cognitive, and social functioning latent factors significantly loaded onto a higher-order successful aging latent factor ( p < .05). Masters athletes had higher physical and social functioning than non-sporting adults ( p < .05). Psychological and cognitive functioning did not differ between groups. Conclusions : Successful aging should be considered as a multi-faceted construct consisting of different domains of functioning for both masters athletes and non-sporting adults. Masters athletes were aged successfully relative to the non-sporting adults across the physical and social functioning domains. Physical, psychological, cognitive, and social functioning domains constitute an appropriate model to use in future experimental research investigating the effect of masters sport for successful aging.